Is Sanctification Real? Empirical Evidence for and against Christian Moral Transformation - Launonen, Lari (Religions, 2023)
According to a widely held view of the New Testament teaching on sanctification; the Holy Spirit brings about a significant moral transformation in the character of every true believer. This claim about Christian moral transformation (CMT) has empirical implications. Thus, its truth can be evaluated from a scientific perspective. Sociological and psychological data on the relationship of religion and morality suggests that (Christian) religion is negatively correlated with undesirable moral behavior such as alcohol and substance abuse, criminal behavior, domestic abuse, and nonmarital sex, and positively correlated with desirable behavior such as helping. While these correlations are consistent with CMT, they do not necessarily serve as good evidence for it, for they can be more naturally explained by situational factors than by character differences between religious and nonreligious people. Some scientific findings serve as evidence against CMT. Religious believers engage in dishonest behavior and porn viewing at least as much as others. There is also a positive correlation between prejudice and conservative Christian beliefs. These correlations cannot be explained by situational factors as easily as the link between religion and desirable moral behavior. Sociological and psychological research; therefore, provides at least a mild challenge for the truth of CMT.